Series of 10 double-duty actions that can be implemented in the areas of health services, social safety nets, education, and food systems to address malnutrition in all its forms - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The article was published in The Lancet as part of its Double Burden of Malnutrition series. In the year after publication, it ranks in the top 5% of all research outputs ever tracked by Altmetric (https://ifpri.altmetric.com/details/72829592).